Calculation of Subsidence due to Longwall Mining with Overburden Grouting and Its Application. (2nd June 2022) - Ma, Hewen; Ji, Yadong; Wang, Shidong
Abstract : This paper presents a prediction method of mining-induced surface subsidence due to longwall mining with overburden grouting, which has been proven an effective method to mitigate the overburden failure. This paper proposes a partial overburden grouting (POG) mining method based on surface subsidence basin inversion and innovative longwall panel layout to mitigate overburden failure and subsidence. A prediction model of surface subsidence with overburden grouting, namely, overburden grouting equivalent calculation model (OGECM), is proposed. In this study, an engineering design process and method of POG was established, the strike and dip excavation length and grouting quantity combined as critical indicators for determining the key parameter in surface basin control. In applications at the field grouting test, the surface subsidence characteristics of POG on the side of the opening line of longwall panel were investigated through surface observation station and estimated surface subsidence reduction ratio based on OGECM with grouting compared with those without. The field measurement validated the new subsidence calculation method. POG technology applied to subsidence control has effectiveness in controlling the surface subsidence to less engineering cost but expanding the applications.